2015
DOI: 10.1007/s10865-015-9629-2
|View full text |Cite
|
Sign up to set email alerts
|

Is procrastination a vulnerability factor for hypertension and cardiovascular disease? Testing an extension of the procrastination–health model

Abstract: Personality is an important epidemiological factor for understanding health outcomes.This study investigated the associations of trait procrastination with hypertension and cardiovascular disease (HT/CVD) and maladaptive coping by testing an extension of the procrastination-health model among individuals with and without HT/CVD. Individuals with self-reported HT/CVD (N = 182) and healthy controls (N = 564), from a community sample, completed an online survey including measures of personality, coping, and healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
1
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 64 publications
1
46
1
6
Order By: Relevance
“…It is also related to disease development, having as a mediator, high stress levels, and greater treatment delays (Sirois and Tosti, 2012). As an example, in a study with persons suffering from hypertension and cardiovascular disease, it was found that procrastination is more closely related to maladaptive general behaviors of the patients than with the missed mandatory health checks, being a factor of primary vulnerability in the disease management (Sirois, 2015). Likewise, there is evidence that points out the relationship between chronic procrastination and stress, which could have consequences such as mental distress (coping inability) and physical distress (Ferrari and Díaz-Morales, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It is also related to disease development, having as a mediator, high stress levels, and greater treatment delays (Sirois and Tosti, 2012). As an example, in a study with persons suffering from hypertension and cardiovascular disease, it was found that procrastination is more closely related to maladaptive general behaviors of the patients than with the missed mandatory health checks, being a factor of primary vulnerability in the disease management (Sirois, 2015). Likewise, there is evidence that points out the relationship between chronic procrastination and stress, which could have consequences such as mental distress (coping inability) and physical distress (Ferrari and Díaz-Morales, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, procrastination has been linked to a number of negative health outcomes, including poor sleep quality (Hairston & Shpitalni, 2016; Sirois, van Eerde, & Argiopoulou, 2015), mood dysregulation (Sirois & Kitner, 2015; Sirois & Pychyl, 2013), and symptoms of depression and anxiety (Beutel et al, 2016). Moreover, there are well-studied links between procrastination and personality variables such as impulsivity and neuroticism (Ferrari, 1993; Schouwenburg & Lay 1995; Steel, 2007; Van Eerde, 2000) that have also been identified as substantial predictors of psychopathology (Hink et al, 2013; Johnson, Caver, & Joormann, 2013).…”
mentioning
confidence: 99%
“…Procrastination is at the center of several societal problems, from the environment to our health [26]. Procrastination is shown as a vulnerability factor for poor adjustment to and management of hypertension and cardiovascular disease [30]. In the procrastination health model, procrastination is suggested to result in less frequent practice of health-promoting behaviors [30, 31].…”
Section: Discussionmentioning
confidence: 99%
“…Procrastination is shown as a vulnerability factor for poor adjustment to and management of hypertension and cardiovascular disease [30]. In the procrastination health model, procrastination is suggested to result in less frequent practice of health-promoting behaviors [30, 31]. Azami-Aghdash et al (2015) reported that procrastination was as a key obstacle to screening of breast cancer [32].…”
Section: Discussionmentioning
confidence: 99%